Rapid experience-dependent plasticity of synapse function and structure in ferret visual cortex in vivo - Yu, Hongbo (National Academy of Sciences, 2011)
The rules by which visual experience influences neuronal responses and structure in the developing brain are not well understood. To elucidate the relationship between rapid functional changes and dendritic spine remodeling in vivo, we carried out chronic imaging experiments that tracked visual responses and dendritic spines in the ferret visual cortex following brief periods of monocular deprivation. Functional changes, which were largely driven by loss of deprived eye responses, were tightly regulated with structural changes at the level of dendritic spines, and occurred very rapidly (on a timescale of hours). The magnitude of functional changes was correlated with the magnitude of structural changes across the cortex, and both these features reversed when the deprived eye was reopened. A global rule governed how the responses to the two eyes or changes in spines were altered by monocular deprivation: the changes occurred irrespective of regional ocular dominance preference and were independently mediated by each eye, and the loss or gain of responses/spines occurred as a constant proportion of predeprivation drive by the deprived or nondeprived eye, respectively.